Porosity and pore connectivity in immature and artificially matured source rock using BIB-SEM, WMI and MIP - Klaver, J.; Schmatz, J.; Krooss, B.; Stockhausen, M.; Schwark, Lorenz; Urai, J. (2016)
© 2016, European Association of Geoscientists and Engineers. All rights reserved.Porosity and pore connectivity in organic-rich shales change with thermal maturity. To document such effects, an immature source rock sample was artificially matured under controlled pressure conditions. Afterwards, its pore structure was compared to the one of an untreated sister sample. Pore space and pore connectivity were investigated by Broad Ion Beam (BIB) polishing and Scanning Electron Microscopy (SEM), Mercury Intrusion Porosimetry (MIP) and Wood's Metal Injection (WMI) followed by BIB-SEM. The SEM images of both samples show cracks indicating enhanced porosity. The organic matter of the matured sample exhibits porosity, however, the portion of identifiable organic matter is drastically lower than in the untreated sample. MIP indicates an increase of macro- and meso-porosity for the matured sample, which is consistent with the BIB-SEM observations. WMI at comparable pressures as MIP also reveals clear differences between the two samples: the untreated sample shows a complex heterogeneous intrusion of the Wood's Metal (WM), filling the matrix for several hundreds of micrometers at various locations while other large parts of the matrix remain unfilled. In contrast, in the matured sample WM was identified throughout the entire sample demonstrating good connectivity.